2021
DOI: 10.3390/ijerph18168591
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Comparison of Mancozeb and Zoxamide Fungicides at Environmentally Relevant Concentrations by an In Vitro Approach

Abstract: Mancozeb (MZ) and zoxamide (ZOX) are fungicides commonly used in pest control programs to protect vineyards. Their toxic and genotoxic potential were investigated in vitro on HepG2 and A549 cell lines at environmentally relevant concentrations. Cytotoxicity, apoptosis, necrosis and intracellular reactive oxygen species (ROS), comet assay and a micronucleus test with CREST immunofluorescence were used. The expression of a panel of genes involved in apoptosis/necrosis (BAX/BCL2), oxidative stress (NRF2), drug me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
3
8
0
Order By: Relevance
“…Moreover, workers exposed to mancozeb in the iodine-deficient area tended to have lower thyroid volumes (≤6 mL). These findings fit well with experimental evidence that the thyroid was a major toxicological target of mancozeb as found both in vitro by Lori et al (2021) and in laboratory animals as summarized by the European Food Safety Authority (EFSA) in a recent evaluation in 2019 [49,50].…”
Section: Health-related Outcomessupporting
confidence: 85%
“…Moreover, workers exposed to mancozeb in the iodine-deficient area tended to have lower thyroid volumes (≤6 mL). These findings fit well with experimental evidence that the thyroid was a major toxicological target of mancozeb as found both in vitro by Lori et al (2021) and in laboratory animals as summarized by the European Food Safety Authority (EFSA) in a recent evaluation in 2019 [49,50].…”
Section: Health-related Outcomessupporting
confidence: 85%
“…At the beginning of this millennium, studies showed that mancozeb can act as an ED, which may affect many bodily functions and cause health hazards (e.g., male infertility) . Researchers have further confirmed its genotoxicity; that is, under acute exposure, it can affect the fertilization capacity of spermatozoa . In another in vitro study, functional impairment of bovine spermatozoa was found after acute exposure to mancozeb .…”
Section: Toxicological Concernsmentioning
confidence: 89%
“…21 Researchers have further confirmed its genotoxicity; that is, under acute exposure, it can affect the fertilization capacity of spermatozoa. 22 In another in vitro study, functional impairment of bovine spermatozoa was found after acute exposure to mancozeb. 23 In a recent study, mancozeb's estrogenic activity was demonstrated.…”
Section: ■ Toxicological Concernsmentioning
confidence: 98%
“…We next studied the mechanism of cytotoxicity induced by the pesticide mixture and DTCs (Figure 4) postulating that maneb and mancozeb may induce apoptosis in hepatocytes since previous publications reported that mancozeb at high concentrations (10 to 300 M) triggered apoptosis in human gastric, colon and hepatoma cells (Kumar et al, 2019 ;Dhaneshwar and Hardej, 2021 ;Lori et al, 2021). We measured caspase 3, 8 and 9 catalytic activities in total cell lysates of hepatocyte-like HepaRG cells exposed to the pesticide mixture or mancozeb alone (Figure 4A).…”
Section: Maneb and Mancozeb Induce Oxidative Stress And Apoptosis In ...mentioning
confidence: 99%